HUBUNGAN DUKUNGAN KELUARGA DAN SOSIAL DENGAN TINGKAT KECEMASAN IBU YANG MEMILIKI BBLR DI RUANG PERINATOLOGI - Adethia, Silvy; Lestari, Nur Eni; Purnamasari, Eka Rokhmiati Wahyu (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Low Birth Weight (LBW) is a cause of high neonatal mortality and can cause various health problems such as growth and development disorders, which ultimately trigger anxiety in mothers. The purpose of this study was to analyze the relationship between family and social support with the anxiety levels of mothers who have LBW babies in the Perinatology. This study used a quantitative design with a cross-sectional approach. The sample in this study were 40 postpartum mothers with LBW babies, selected through consecutive sampling technique. The independent variables included family support and social support, while the dependent variable was the level of maternal anxiety. Data were analyzed using the Spearman rank test. The results showed that the majority of mothers experienced moderate anxiety (80%), received sufficient family support (45%), and received high social support (75%). There was a significant relationship between family support and maternal anxiety levels (p = 0.044; r = -0.320) and a very significant relationship between social support and maternal anxiety levels (p = 0.000; r = -0.613). The conclusion of this study is that the higher the family and social support received by mothers, the lower the level of anxiety they feel, although support is not the only determining factor in anxiety. The initial hypothesis stating there is no relationship is rejected, because there is evidence of a significant relationship.